Three-dimensional quantitative assessment of surgical stability and condylar displacement changes after counterclockwise maxillomandibular advancement surgery: Effect of simultaneous articular disc repositioning - Gomes, Liliane Rosas [UNESP]; Soares Cevidanes, Lucia Helena; Gomes, Marcelo Regis; Oliveira Ruellas, Antonio Carlos de; Obelenis Ryan, Daniel Patrick; Paniagua, Beatriz; Wolford, Larry Miller; Goncalves, Joao Roberto [UNESP] (Elsevier B.V., 2018)
Introduction: In this study, we quantitatively assessed 3-dimensional condylar displacement during counterclockwise maxillomandibular advancement surgery (CMMA) with or without articular disc repositioning, focusing on surgical stability in the follow-up period. Methods: The 79 patients treated with CMMA had cone-beam computed tomography scans taken before surgery, immediately after surgery, and, on average, 15 months postsurgery. We divided the 142 condyles into 3 groups: group 1 (n = 105), condyles of patients diagnosed with symptomatic presurgical temporomandibular joint articular disc displacement who had articular disc repositioning concomitantly with CMMA; group 2 (n = 23), condyles of patients with clinical verification of presurgical articular disc displacement who had only CMMA; and group 3 (n = 14), condyles of patients with healthy temporomandibular joints who had CMMA. Presurgical and postsurgical 3-dimensional models were superimposed using voxel-based registration on the cranial base. Three-dimensional cephalometrics and shape correspondence were applied to assess surgical and postsurgical displacement changes. Results: Immediately after surgery, the condyles moved mostly backward and medially and experienced lateral yaw, medial roll, and upward pitch in the 3 groups. Condyles in group 1 showed downward displacement, whereas the condyles moved upward in groups 2 and 3 (P 0.001). Although condylar displacement changes occurred in the 3 groups, the overall surgical procedure appeared to be fairly stable, particularly for groups 1 and 3. Group 2 had the greatest amount of relapse (P 0.05). Conclusions: CMMA has been shown to be a stable procedure for patients with healthy temporomandibular joints and for those who had simultaneous articular disc repositioning surgery.